Systemic Design Approach to the Finnish Funeral Ecosystem - Kuronen, Marja (fi=Lapin yliopisto|en=University of Lapland|, 2022)
In our time, funerals have become more private within the community, and the processes related to dying have shifted from involving only relatives to having to include various professionals, hospitals, morgues and crematoriums. Relatives are now bystanders during their loved one’s funeral process, and the lack of rituals that fit one’s life view can result in unprocessed grief. In many ways, the post-mortem process has become effective, and efficient but often meaningless for relatives. The process is governed by laws and operated by different administrations, churches, agencies, and ministries. In addition, social relationships, paradigms, and norms affect bereavement’s experience as they are arranging funerals. The study explores how design thinking and systems thinking can be applied in understanding and developing Finnish funeral services and processes. By utilizing frameworks like systems-oriented design and service design it is possible to understand and make initiatives towards a more socially sustainable and inclusive funeral future. With the systems-oriented design, it is possible to observe the operating environment with wider lenses and the approach enables identifying the complexity of the systems that are included in the dynamics and decision-making of the entire ecosystem. While the service design approach provides processes and tools to understand the end-user and develop services that are meaningful for them. The master’s thesis at hand is a continuation of author’s first master’s thesis “Funeral service development for the needs in the near future” (Master’s degree in Service design and Leadership / Novia UAS) in which she discovered the future demands for funeral services and processes from the relative’s point of view. In the thesis at hand, she zooms out from the relative’s angle to the ecosystem and culture that creates the relative’s experience. The aim of the master’s thesis is to explore the Finnish funeral ecosystem and its dynamics to make initiatives towards a change that serves next ...